1990
DOI: 10.1042/bj2680669
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic analysis of regeneration by dilution of a covalently modified protein

Abstract: An analysis of regeneration by dilution of a covalently modified protein is presented. It is shown that, when protein regeneration is realized through the intermediacy of a protein-modifying agent adsorptive complex, the reaction is described by a summation of two exponential functions of reaction time plus a constant-term equation. The conditions whereby this equation reduces to a single-exponential equation are delineated. It is shown that, when protein regeneration is described by a single-exponential funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 10 publications
(7 reference statements)
0
5
0
Order By: Relevance
“…Thermodynamic and kinetic analysis of protein modification and enzyme inactivation reactions and of regeneration by dilution of covalently modified proteins have been performed (34)(35)(36). Examples are known in which kinetic properties have been altered after modification of an enzyme and there are also cases in which new catalytic activities have been introduced [37,38].…”
Section: Internal Modificationsmentioning
confidence: 99%
“…Thermodynamic and kinetic analysis of protein modification and enzyme inactivation reactions and of regeneration by dilution of covalently modified proteins have been performed (34)(35)(36). Examples are known in which kinetic properties have been altered after modification of an enzyme and there are also cases in which new catalytic activities have been introduced [37,38].…”
Section: Internal Modificationsmentioning
confidence: 99%
“…Briefly, samples of MNL were inactivated by 0.2 mM MOI and then diluted 10, 15, 25, 50, and 100-fold with citrate buffer, pH 5.5. The time course for recovery of MNL activity was monitored, and the data from each dilution were plotted as In [(E^ -EJ/ÇE,^ -E^] vs time 25 , where E 0 is the enzyme activity at the start of the dilution-induced reactivation event, Έ^ is the activity at reaction time t, and Egq is the activity at equilibrium (Figure 3.7).…”
Section: Recovery Of Activity By Dilutionmentioning
confidence: 99%
“…The slopes of the five lines in Figure 3.7 were then used to determine &_ 2 according to equation 3.Ó 25 :…”
Section: Recovery Of Activity By Dilutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Protein modification reactions may exhibit an enhancement of rate when compared with the reaction of the same modifying agent with a micromolecular model compound possessing the same modifiable group as the protein under study. The question of the maximum extent of rate-enhancement of protein modification may be answered by the acceptance of certain formalistic assumptions, namely the description of the protein modification reaction by a single exponential function of reaction time, and also of an acceptable rate of dilution-induced enzyme re-activation (Rakitzis, 1989(Rakitzis, , 1990. In the present paper it is shown that the maximunj extent of affinity-mediated rateenhancement of protein modification may be determined if the entropy of activation of the reaction of the modifying agent under study with a model micromolecular compound is known.…”
Section: Introductionmentioning
confidence: 99%